The Influence of User-Generated Content (UGC), Electronic Word of Mouth (e-WOM), and Perceived Product Quality on Purchase Intention of Somethinc Products (Case Study on Followers of TikTok @somethincofficial) - Zefania Mikha Manurung; R. Yuniardi Rusdianto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study utilizes a quantitative approach aimed at determining both the partial and simultaneous effects of user-generated content, electronic word of mouth, and perceived product quality on purchase intention for Somethinc products. With the rapid growth of digital marketing, especially on platforms like TikTok, gaining insight into these factors plays a vital role in brands' efforts to influence consumer behavior. The study’s population consists of followers of the @somethincofficial TikTok account. A total of 204 respondents were selected using the Slovin formula, with purposive sampling applied based on specific criteria such as TikTok users born in 1997-2012, followers of the @somethincofficial TikTok account, knowing the Somethinc brand, and having seen content or reviews about Somethinc products. Multiple linear regression analysis was used for data analysis. This study reveals that user-generated content, electronic word of mouth, and perceived product quality, both simultaneously and partially, exert a significant influence on purchase intention for Somethinc products.